Actinomycoses masquerading as an abdominal intramuscular tumour - Noor Afi dah MS; Noor Laili MM; Koh SK; Lee YL; Maninder Kaur; Nur Syahrina Rahim (College of Pathologists, Academy of Medicine Malaysia, 2024)
Introduction: Actinomycosis is a chronic abscess-forming disease predominantly caused by Actinomyces israelii. Long-term use of an IUCD is known as a risk factor for pelvic actinomycosis. However the involvement of the abdominal wall is a rare clinical entity. We report an unusual case of abdominal actinomycosis presenting as abdominal wall intramuscular mass. Case: A 41- year-old lady para 3 presented with 3 months history of right iliac fossa pain associated with an infi ltrative abdominal wall mass. There was also associated loss of weight and appetite. Her white cell count was raised but there was no history of fever. She was on IUCD contraception for the past 3 years and her menses were otherwise regular. The mass was then excised in view of clinical and radiological suspicion of malignancy. The histopathological fi ndings of the mass showed presence of multiple abscesses containing Actinomyces colonies within the muscular wall and adjacent tissue, surrounded by chronic infl ammation and tissue fi brosis. She had her IUCD removed and was started with antibiotic therapy with serial CT scan surveillance. Conclusion: This case illustrates that actinomycoses can mimic the presentation of a malignancy only to be confi rmed histologically as an infection. Recognition of the various ways of presentation for Actinomyces is essential for appropriate management of the patients.